Survival advantage of partial over radical nephrectomy in patients presenting with localized renal cell carcinoma - Roos, Frederik C.; Steffens, Sandra; Junker, Kerstin; Janssen, Martin; Becker, Frank; Wegener, Gerd; Brenner, Walburgis; Steinestel, Julie; Schnoeller, Thomas J.; Schrader, Mark; Hofmann, Rainer; Thueroff, Joachim W.; et al. (BMC Cancer, 2014)
Partial nephrectomy (PN) preserves renal function and has become the standard approach for T1a renal cell carcinoma (RCC). However, there is still an ongoing debate as to which patients will actually derive greater benefit from partial than from radical nephrectomy (RN). The aim of this study was to retrospectively evaluate the impact of the type of surgery on overall survival (OS) in patients with localized RCC.Renal surgery was performed in 4326 patients with localized RCC (pT <= 3a N/M0) at six German tertiary care centers from 1980 to 2010: RN in 2955 cases (68.3%), elective (ePN) in 1108 (25.6%), and imperative partial nephrectomy (iPN) in 263 (6.1%) cases. The median follow-up for all patients was 63 months. Kaplan-Meier and Cox regression analyses were carried out to identify prognosticators for OS.PN was performed significantly more often than RN in patients presenting with lower tumor stages, higher RCC differentiation, and non-clear cell histology. Accordingly, the calculated 5 (10)-year OS rates were 90.0 (74.6)% for ePN, 83.9 (57.5)% for iPN, and 81.2 (64.7)% for RN (p < 0.001). However, multivariate analysis including age, sex, tumor diameter and differentiation, histological subtype, and the year of surgery showed that ePN compared to RN still qualified as an independent factor for improved OS (HR 0.79, 95% CI 0.66-0.94, p = 0.008).Even allowing for the weaknesses of this retrospective analysis, our multicenter study indicates that in patients with localized RCC, PN appears to be associated with better OS than RN irrespective of age or tumor size.
EVALuna2:6665